Relationship between job stress, thinking style and symptoms of post-traumatic stress disorder in mental health nurses - Liu, Wuyi; Sun, Lin; Yin, Xunbao; Zhao, Huan; Zhu, Guohui; Lian, Bo; Sun, Hongwei (Frontiers in Public Health, 2022)
Introduction: Mental health nurses are often exposed to stressful events which may lead to feeling of stress in their daily work, and this feeling has a profound impact on nurses' mental health. Aim: This study aimed to evaluate the relationship between job stress, thinking style and symptoms of post-traumatic stress disorder (PTSD) of mental health nurses, and to explore the mechanism of job stress and thinking style on symptoms of PTSD. Method: This cross-sectional study collected related data of 351 mental health nurses in China, and the data was analyzed by PROCESS macro for SPSS. Results: The results showed that 18.2% of mental health nurses had the symptoms of PTSD. Thinking style (monarchic thinking style, anarchic thinking style and external thinking style) played a moderating role in the predictive effects of job stress on the symptoms of PTSD. Discussion: The research pointed out the relationship between job stress and symptom of PTSD, and clarified the critical role of thinking style among mental health nurses. Implications for Practice: It is recommended that organizations should enact effective policy and intervention programs to reduce job stress and PTSD symptoms of mental health nurses which may improve their mental health level.